Penerapan Pendidikan Karakter Berbasis Pancasila Pada Mata Pelajaran Budi Pekerti Dan Nasionalisme - Clara Widhani Fauziah; Natasya Karla; Rr.Dinda Bayu Putri; Tasya Maria Agustin Marpaung (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the implementation of character education based on Pancasila values through the local content subject